Mind Mapping and Positive Mental Attitude to Enhance Secretarial Duties - Benedicta Djarwati Muljani; Eric Sulindra; Tuti Hartani (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2023)
Mind mapping is a powerful graphic technique that provides universal keys to unlocking the brain's potential. It has been proven through studies that work performance, including secretarial duties, are affected significantly by how an individual manage their thinking. Hypothetically, mind-mapping, one of the techniques to organize thoughts and produce creative ideas, could help enhance desired mental attitude (one of our mind’s product) which in turn direct the secretarial duties completion with the desired result. The study is observing and finding patterns of how mind-mapping affects one’s mental attitude and enhance her secretarial duties performance. The findings show that the mind mapping skills support the functions of an office administration personnel in planning and executing plans. The respondents showed they used graphs, figures, and symbols in planning and executing the plan. The findings regarding mental attitude supporting Secretarial Skills also indicate that most of the mental attitude aspects support secretarial skills.